2015
DOI: 10.18052/www.scipress.com/ilns.38.46
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Plant Density of Okra and Intercropping Effects on Yields of Egusi Melon-Okra Mixture, at Makurdi, Nigeria

Abstract: ABSTRACT.A field experiment was conducted from August to November, during the 2012 and 2013 cropping seasons at the Research Farm, University of Agriculture, Makurdi, Nigeria, to identify the optimum plant density of okra and intercropping effects on yields of egusi melon-okra mixture and to assess the yield advantages of the intercropping system. The experiment was a 3x3 split plot arrangement of treatments, fitted in a randomized complete block design (RCBD), replicated four times. The intercropping (sole eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
3
2
0
Order By: Relevance
“…Phenological and growth response of Tomato Days to 50% flowering and days to physiological maturity of tomato The analysis of variance showed that days to 50% flowering and days to physiological maturity of tomato were not significantly affected by varieties, there population density and interaction effect (Appendix Table 1). The result agreed with Ijoyah et al (2015) who reported that population densities of okra did not significantly affected days to attain 50 % flowering for okra in okra-egusi melon intercropping. Cropping system is not significantly affected days to 50% flowering and days to physiological maturity of tomato.…”
Section: Results and Disscusionsupporting
confidence: 91%
See 4 more Smart Citations
“…Phenological and growth response of Tomato Days to 50% flowering and days to physiological maturity of tomato The analysis of variance showed that days to 50% flowering and days to physiological maturity of tomato were not significantly affected by varieties, there population density and interaction effect (Appendix Table 1). The result agreed with Ijoyah et al (2015) who reported that population densities of okra did not significantly affected days to attain 50 % flowering for okra in okra-egusi melon intercropping. Cropping system is not significantly affected days to 50% flowering and days to physiological maturity of tomato.…”
Section: Results and Disscusionsupporting
confidence: 91%
“…This might be due to the highest number of primary branches per plant is obtained due to 50% population density those branches forced to produce more number of fruits per plant when the net assimilation rate was higher. This is supported by the results of Ijoyah et al (2015) that population density of okra significantly increased the number of egusi melon fruits per plant, number of egusi melon seeds per fruit, weight of seeds per fruit and yield of egusi melon in okra-egusi melon intercropping, Planting of okra at the population density of 40,000 plants ha -1 significantly increased yield of egusi melon, compared to when okra was sown at the population density of 50,000 plants ha -1 . This result disagree with the findings of Tuan and Mao (2015) and Tesfaye (2008) who reported that fruit number per plant was significantly influenced by plant density but the low plant density resulting in significantly more fruit number as compared to high plant density.…”
Section: Number Of Fruit Per Plantsupporting
confidence: 76%
See 3 more Smart Citations